Analisis Penerapan Murottal Al-Quran Terhadap Tanda Dan Gejala Halusinasi Pendengaran Ny. R Di Wilayah Kerja Puskesmas Panti Kabupaten Jember - Juwita Puspita Rini Saputri; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Amalia Kusumaningsih (Health and Technology Journal (HTechJ), 2024)
Schizophrenia is a serious mental health problem where one of the symptoms is hallucinations. Signs and symptoms of hallucinations include feeling more comfortable with their situation, the client is seen laughing and talking to himself or expressing things that are not actually real, so pharmacological and non-pharmacological therapy management is needed. One of them is by providing Murottal Al-Qur'an therapy. The aim of this research is to explain nursing care and determine the analysis of Al-Quran murottal therapy on reducing the signs and symptoms of auditory hallucinations experienced by patients. This research design uses descriptive research with a case study method. Therapy is given for 7 days for 15 minutes by listening to the chanting of holy verses from the Koran, one of which is Surah Ar-Rahman and Surah Al-Jinn. The results of the research were a decrease in the signs and symptoms of hallucinations in clients and the ability to control their hallucinations by carrying out positive activities, conversing with people around them and murottalizing the Koran. Providing Al-Quran murottal therapy can reduce the client's signs and symptoms of hallucinations, namely daydreaming, isolating himself, smiling, talking to himself, lack of eye contact and hearing voices that are not real.